Peran Zakat Sebagai Instrumen Penguatan Ekonomi Mikro Islam - Zuni Rohmawati; Eny Latifah (Jaanur Elbarik Indonesia, 2025)
The purpose of this study is do determine the extent of the role of zakat as an instrument of strengthening in islamic microeconomics. This research method is qualitative with a type of literature review (library). The result of the study are first, the effectiveness of the role of zakat management by zakat amil institutions: can create proffesionalism and transparency through the zakat management system. Second, the roe of zakat management in economic empowerment: increasing the empowerment of MSMEs, supporting mustahik in developing bussinesses, increasing economic sustainability, reducing poverty, increasing income, creating job opportunities, supporting inclusive and sustainable economic growth at the micro level. Third, the role of zakat in empowering MSMEs and alleviating poverty: building a more inclusive economic ecosystem: creating sustainable empowerment, increasing the income of zakat recipients and opportunities to grow into independent entrepreneurs: providing zakat funds to mustahik in the form of bussiness capital, alonh with training and mentoring. Fourth, the role of zakat in optimizing strategies for microeconomic empowerment: integration of productive zakat with MSME empowerment: Data based approach and digital technology: multi stakeholder collaboration: long term impact evaluation.